Prevalence of postconcussion syndrome after mild traumatic brain injury in young adults from a single neurosurgical center in East Coast of Malaysia - Balakrishnan, Buveinthiran; Mohd Rus, Razman; Kin, Hup Chan; Martin, Arvind Gerard; Awang, Mohamed Saufi (Wolters Kluwer - Medknow, 2019)
Context: Postconcussion syndrome (PCS) is a set of symptoms occurred after a mild traumatic brain injury (MTBI). Aims: This study aims to determine the prevalence of PCS in a young adult population from a single Neurological Centre in Malaysia’s East Coast and to evaluate the factors associated with PCS in MTBI patients. Settings and Design: This was a cross‐sectional study conducted in a Neurological Centre at Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia, from January 2016 to December 2016. Subjects and Methods: A total of 209 patients; 133 males and 76 females, in the age range of 16–84 years, were randomly recruited for this study. All the selected patients were subjected to the checklist for diagnosis of PCS as per International Statistical Classi cation of Diseases and Related Health Problems 10th edition classi cation at a 2‐week interval. Statistical Analysis Used: Descriptive statistic and Multivariable Logistic Regression Model were used for frequency and percentage analyses of categorical variables, using SPSS version 23.0. Results: Only 20 patients were identi ed with PCS. There were more female (70%) patients with PCS than the male (30%) patients. The prevalence of PCS for 2 weeks, 3 and 6 months since injuries were 9.6%, 8.1%, and 8.1% respectively. Majority (80%) of the patients were found to have PCS due to road traf c accidents, while the remaining were attributed to assault (15%), and falls (5%). Among the sample population, 25% were smokers, while 10% of them had either skull fracture or premorbidity. Conclusion: Less than 10% of patients with MTBI had PCS after 6 months’ following trauma. None of the variables tested were signi cant factors for the development of PCS symptoms.